Maternal ability to take care of children exposed to HIV - Julyana Gomes Freitas; Léa Maria Moura Barroso; Marli Teresinha Gimeniz Galvão (Universidade de São Paulo, 2013)
OBJECTIVE: to assess the ability of mothers to take care of children exposed to HIV, using the Assessment Scale of Care Skills for Children Exposed to HIV at Birth and to check the association between the scale dimensions and maternal characteristics. METHOD: this cross-sectional study involved 62 HIV+ mothers whose children of up to one year old had been exposed to the virus at birth. The Assessment Scale of Care Skills for Children Exposed to HIV at Birth consists of 52 items and five dimensions, indicating high, moderate or low care ability. RESULTS: 72.7% of the mothers appropriately offered zidovudine syrup; 86.0% were highly skilled to prepare and administer milk formula; 44.4% were moderately able to prepare and administer complementary feeding; 76.5% revealed high ability to administer prophylactic treatment against pneumonia and 95.3% demonstrated high abilities for clinical monitoring and immunization. Significant associations were found between some maternal variables and the scale dimensions. CONCLUSION: the scale permits the assessment of maternal care delivery to these children and the accomplishment of specific child health interventions.